2013
DOI: 10.2139/ssrn.2335990
|View full text |Cite
|
Sign up to set email alerts
|

Do Female Officers Improve Law Enforcement Quality? Effects on Crime Reporting and Domestic Violence Escalation

Abstract: We study the impact of the integration of women in US policing between the late 1970s and early 1990s on violent crime reporting and domestic violence escalation. Along these two key dimensions, we find that female officers improved police quality. Using crime victimization data, we find that as female representation increases among officers in an area, violent crimes against women in that area, and especially domestic violence, are reported to the police at significantly higher rates. There are no such effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…numerous studies have shown that diverse teams perform better than homogenous ones (Chen and Levine 2016;Hunt et al 2015;Hoogendoorn et al 2013). This evidence holds true both for police forces (asquith 2016;Miller and Segal 2013) and for military teams (Hörst et al forthcoming,(18)(19)(20)(21). it is important to note that the argument here is not about women being more peaceful than men but about women bringing a different perspective and skill set to the table.…”
Section: Why Is Gender Balance In Csdp Missions and Operations Importmentioning
confidence: 86%
“…numerous studies have shown that diverse teams perform better than homogenous ones (Chen and Levine 2016;Hunt et al 2015;Hoogendoorn et al 2013). This evidence holds true both for police forces (asquith 2016;Miller and Segal 2013) and for military teams (Hörst et al forthcoming,(18)(19)(20)(21). it is important to note that the argument here is not about women being more peaceful than men but about women bringing a different perspective and skill set to the table.…”
Section: Why Is Gender Balance In Csdp Missions and Operations Importmentioning
confidence: 86%
“…Whilst law enforcement has not usually been perceived to have an explicit public health role, there has recently been growing interest in the many ways in which law enforcement, especially police, contribute to the public health mission (Van Dijk & Crofts, 2017). Looking at a specific policehealth nexus, women's participation in policing has shown benefits associated with responsiveness to-and reduction of-gender-based violence (Miller & Segal, 2016). Women officers are also less likely to use excessive force (Lonsway, 2000;Porter & Prenzler, 2017;Schuck & Rabe-Hemp, 2007).…”
Section: Researching Gender and Law Enforcement As Public Health Inputmentioning
confidence: 99%
“…While the institution with the responsibility for crime detection, the police, has been the focus of much recent work, most such efforts have been directed to studying its reduced form effect on crime. Typical approaches include examining whether police numbers (Levitt, 1997), police composition (McCrary 2007, Miller andSegal 2014) or high visibility patrolling (Di Tella and Schargrodsky 2004, Klick and Tabarrok 2005, Evans and Owens 2007and Draca et al 2011 are associated with lower crime rates. The implicit assumption is that a change in these variables can lead to higher chances of catching offenders, which has an immediate deterrence effect as well as an incapacitation effect over longer horizons.…”
Section: Introductionmentioning
confidence: 99%